Can WTO Member States Rely on Citizen Concerns to Prevent Corporations from Importing Goods Made from Child Labour? - Aleydis Nissen (Utrecht Law Review, 2018)
There has been a polarised debate on the desirability of import restrictions to increase corporate accountability for child labour that occurs in global supply chains. Some scholars have indicated that states in favour of imposing import restrictions could sidestep this debate relying upon the perceptions that people in the importing market might have. They have based this argument on the case law of the World Trade Organization's Dispute Settlement Mechanism (WTO DSM). The attitude-behaviour gap has, however, been largely overlooked in their analyses. This behavioural phenomenon provides an explanation as to why there is an inconsistency between what people value or believe and what they actually do. This essay revisits the WTO DSM's case law in order to determine whether such values or beliefs might justify import restrictions. On balance, this essay finds that the WTO DSM has not sufficiently taken the attitude-behaviour gap into account in its interpretation of Article III(4) and Article XX(a) 1994 General Agreement on Tariffs and Trade (GATT).
Keywords: J08; P37; P36; F13; F23; D18; 330; consumer choices; behavioural international law; social clause; labour standards; public morals